Synthesis and characterisation of rylene diimide dimers using molecular handcuffs. Issue 13 (22nd February 2019) - Yang, Lixu; Langer, Philipp; Davies, E. Stephen; Baldoni, Matteo; Wickham, Katherine; Besley, Nicholas A.; Besley, Elena; Champness, Neil R.
Abstract : Mechanically interlocked handcuffs provide a strategy to study rylene diimide dimers and to investigate their electronic and magnetic properties. Abstract : A strategy for positioning, and loosely connecting, molecules in close proximity using mechanically interlocked handcuffs is described. The strategy is demonstrated using rylene diimides, creating dimeric structures in which two components are linked through pillar[5]arene/imidazolium rotaxanes. Investigation of the resulting molecules demonstrates intriguing and new properties that arise from placing these redox active dye molecules together, allowing interactions, whilst allowing the molecules to separate as required. In particular we observe excimer emission from a perylene diimide dimer handcuff and the formation of an unusual radical anion π-dimer upon double reduction of the same molecule. The latter exhibits a unique visible absorption profile for a PDI-based molecule. We demonstrate the flexibility of our approach by making an unprecedented mixed perylene diimide/naphthalene diimide dimer which also reveals interactions between the two components. Our synthetic strategy facilitates the creation of unusual dimeric structures and allows the investigation of intermolecular interactions and the effects they have on electronic and magnetic properties.